Frontiers in Hybrid Ion Capacitors: A Review on Advanced Materials and Emerging Devices. Issue 8 (17th March 2021) - Naskar, Pappu; Kundu, Debojyoti; Maiti, Apurba; Chakraborty, Priyanka; Biswas, Biplab; Banerjee, Anjan
Abstract: Hybrid supercapacitors are the most desirable electrochemical energy storage devices, owing to their versatile and tunable performance characteristics, specifically in energy and power densities, towards applications in research and development. Construction‐wise, optimized assembly of batteries (energy devices) and supercapacitors (power devices) are the key for hybrid supercapacitors. Based on scientific advancements and technological achievements, hybrid ion capacitors are the most important segments in hybrid supercapacitors, as well as in the overall energy storage arena. Herein, opportunities and challenges of hybrid ion capacitors are intensively addressed in light of lithium‐ion, sodium‐ion, potassium‐ion, magnesium‐ion, calcium‐ion, zinc‐ion, and aluminum‐ion capacitors. The historical origins and their developmental pathways are identified for each type of capacitor. Possible classes of materials for every hybrid ion capacitor are discussed, and relevant mechanisms are demonstrated. These discussions reveal that a rich materials bank exists for lithium‐ion, sodium‐ion, and zinc‐ion capacitors, but the same is not applicable for potassium‐ion, magnesium‐ion, calcium‐ion, and aluminum‐ion capacitors. Consequently, such hybrid ion capacitors have not yet reached the level of commercial benchmarks like lithium‐ion, sodium‐ion, and zinc‐ion capacitors. However, this Review focuses on mostly full‐cell device data that synchronize the performances of practical scaled‐up systems. Several electrolytes based on solvent media (aqueous, organic, and ionic liquid), phase (liquid, gel, and solid), and redox activity (active and passive) are exemplified in different sections of hybrid ion capacitors. Various device constructions are elaborated upon, such as liquid‐electrolyte devices, polymeric gel devices, all‐solid‐state devices, flexible‐cum‐wearable devices, microdevices, solar‐charging devices, and so forth. The Review culminates with feasible future directions for the commercial success of hybrid ion capacitors, which are in the nascent stages of developments. To the best of our knowledge, it is the first holistic account of hybrid ion capacitors from their historical perspectives to present developments. Abstract : Keeping it real : The design and development of hybrid ion capacitors are discussed as green and sustainable energy storage solutions. Hybrid ion capacitors are constructed through the optimized ensembles of metal‐ion battery chemistries (Li, Na, K, Mg, Ca, Zn, and Al‐ion system) and supercapacitors (electrical double‐layer capacitors and pseudocapacitors). The historical perspectives and developmental pathways of the entire hybrid ion capacitor family are elaborated upon. However, this Review focuses on advanced materials, relevant mechanisms, and the resulting prototype fabrications for real‐field applications.